XFEM analysis of a 2D cracked finite domain under thermal shock based on Green-Lindsay theory. (15th March 2018) - Zarmehri, Navid Roshani; Nazari, Mohammad Bagher; Rokhi, Masoud Mahdizadeh
Highlights: XFEM analysis of thermal fracture based on Green-Lindsay model is performed. The interaction integral is developed to account dissipated energy in Green-Lindsay model. The effect of the speed of temperature and stress waves on the time history of stress intensity factors is discussed. Time history of the thermal SIFs based on classic and G-L model are compared. Abstract: In this paper, the extended finite element method is implemented to extract stress intensity factors (SIFs) for a stationary crack in an isotropic 2D finite domain under thermal shock. The fully coupled generalized thermoelasticity theory based on Green-Lindsay (G-L) model is considered. The interaction integral is developed to compute the stress intensity factors in which the dissipated part of the strain energy density is accounted to preserve domain-independency of. The Newmark time integration scheme is used to solve semidiscrete governing equations. According to the results, the speed of stress and temperature waves controls the time variations of stress intensity factors especially at early times of the thermal shock.